RANCANG BANGUN RANGKA MESIN PENCETAK BRIKET BATOK KELAPA SKALA UMKM - Mustofa, Muhamad Rizky Asrof; Saleh, Agus (Jurnal Mahasiswa Terapan, 2024)
Coconut trees grow well in tropical climates, especially in Indonesia. The Food and Agriculture Organization (FAO) reported Indonesia as the world's largest coconut producer in 2016, with 19 million tons of coconut production (31% of the world total) and a coconut plantation area of ​​3.08 million hectares.  Coconut shell solid waste is one of the major wastes produced from coconut production. The results of making a coconut shell briquette printing machine on a UMKM scale show that the machine frame produces the required safety factor value for components capable of withstanding dynamic loads, namely 1-3. The complete frame simulation results can be seen from the simulation results showing that the design of the briquette printing frame is still safe enough to withstands loads up to 30 kg.